Optimization of adeno-associated viral vector-mediated transduction of the corticospinal tract: comparison of four promoters - Nieuwenhuis, Bart; Haenzi, Barbara; Hilton, Sam; Carnicer-Lombarte, Alejandro; Hobo, Barbara; Verhaagen, Joost; Fawcett, James W (Gene therapy, 2021)
Adeno-associated viral vectors are widely used as vehicles for gene transfer to the nervous system. The promoter and viral vector serotype are two key factors that determine the expression dynamics of the transgene. A previous comparative study has demonstrated that AAV1 displays efficient transduction of layer V corticospinal neurons, but the optimal promoter for transgene expression in corticospinal neurons has not been determined yet. In this paper, we report a side-by-side comparison between four commonly used promoters: the short CMV early enhancer/chicken β actin (sCAG), human cytomegalovirus (hCMV), mouse phosphoglycerate kinase (mPGK) and human synapsin (hSYN) promoter. Reporter constructs with each of these promoters were packaged in AAV1, and were injected in the sensorimotor cortex of rats and mice in order to transduce the corticospinal tract. Transgene expression levels and the cellular transduction profile were examined after 6 weeks. The AAV1 vectors harbouring the hCMV and sCAG promoters resulted in transgene expression in neurons, astrocytes and oligodendrocytes. The mPGK and hSYN promoters directed the strongest transgene expression. The mPGK promoter did drive expression in cortical neurons and oligodendrocytes, while transduction with AAV harbouring the hSYN promoter resulted in neuron-specific expression, including perineuronal net expressing interneurons and layer V corticospinal neurons. This promoter comparison study contributes to improve transgene delivery into the brain and spinal cord. The optimized transduction of the corticospinal tract will be beneficial for spinal cord injury research.
Keywords: transdukce genetická; myši; Transduction, Genetic; Dependovirus; genetické vektory; krysa rodu Rattus; transgeny; Genetic Vectors; Promoter Regions, Genetic; Animals; Transgenes; promotorové oblasti (genetika); Mice; Rats; Pyramidal Tracts; zvířata; pyramidové dráhy